Relationship between nutritional status, physical activity and quality of life among gastrointestinal cancer survivors - Abu Zaid, Zalina; Lee, V. C.; Kandiah, Mirnalini (Nutrition Society of Malaysia, 2012)
Introduction: The objective of this study was to determine the relationship between nutritional status, physical activity and quality of life among gastrointestinal cancer survivors. Methods: A cross-sectional study was conducted among gastrointestinal cancer survivors attending the oncology outpatient clinic in Hospital Selayang, Malaysia. Results: A total of 70 gastrointestinal cancer survivors with a mean age of 52.54 ± 14.59 years (95% CI: 47.48 – 57.60) were included in this study. Results showed that 40% of the patients were classified as having low physical activity. The mean Patient Generated Subjective Global Assessment (PGSGA) score was 10.27 ± 7.36 (95% CI: 8.23 – 12.31) and nearly half the patients (48.6%) were identified as severely malnourished (Stage C). Mean Gastrointestinal Quality of Life Index (GQLFI) score was 103.57 ± 23.85 (95% CI: 92.94 -114.20), and about 24.3% of the patients were classified as having a low quality of life. Pearson’s correlation test showed a highly significant negative relationship between nutritional status and quality of life (r=-0.661, p<0.001) indicating the better the nutritional status (low total mean score of PGSGA), the better the quality of life of the survivors (high total mean score of GQLFI). There was a significant negative relationship between physical activity level and nutritional status score (r=-0.309, p<0.01), indicating the higher the physical activity level of the patients (high MET-min/week), the better their nutritional status (low total mean score of PGSGA). Conclusion: This study shows a significant relationship between nutritional status, physical activity and quality of life among gastrointestinal cancer survivors. Those low in nutritional status have a low quality of life while survivors with higher nutritional status have a better quality of life.